Motivation for Intelligence-Service Work – The German Democratic Republic State-Security - Helmut Muller-Enbergs (Romanian Intelligence Studies Review, 2023)
Though the interest in the motivation behind intelligence work is great, hardly any empirical investigations have been published. This may be due to the subject itself being difficult to research. Intelligence services, secret police and the police hardly report openly on such matters, especially considering their reluctance to expose their conspiratorial personnel in academic investigations. Included in the findings published by “experts” are mostly testimonials and evaluations from criminal proceedings involving informers, which, under empirical aspects, hardly lead to valid results. The group of defendants poses only an exposed minority, presumably aware of its advantage in criminal law, and consequently unlikely to venture more “primitive” motives. The greater number of testimonials, mostly communist and post-communist memoirs, is similarly unhelpful since the former agents, messengers or spies emphasis their ideals as motivation. In contrast, the confidants tending towards materialism report less openly about the structure of their motivation.